2003
DOI: 10.1046/j.1460-9592.2003.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Class I Antiarrhythmic Drug Induced T Wave Alternans in an Asymptomatic Brugada Syndrome Patient

Abstract: A 53-year-old man with an abnormal ECG was referred to the Nihon University School of Medicine. The 12-lead ECG showed right bundle branch block and saddleback-type ST elevation in leads V1-V3 (Brugada-type ECG). Signal-averaged ECG showed positive late potentials. Double ventricular extrastimuli (S1: 500 ms, S2: 250 ms, S3: 210 ms) induced VF. Amiodarone (200 mg/day) was administered for 6 months and programmed ventricular stimulation was repeated. VF was induced again by double ventricular stimuli (S1: 600 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…[15][16][17] Takagi et al demonstrated that pilsicainide induced T-wave alternans, increased the frequency of multiform premature ventricular contractions, and eventually VF developed. 16 Morita et al demonstrated in an invitro canine tissue model of BS that T-wave alternans was caused by adjacent regions having action potentials (APs) with longer duration and larger domes or without domes coexisting simultaneously in the epicardium, and compared with the shallow T waves, deep T waves were associated with epicardial APs having longer durations and larger domes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] Takagi et al demonstrated that pilsicainide induced T-wave alternans, increased the frequency of multiform premature ventricular contractions, and eventually VF developed. 16 Morita et al demonstrated in an invitro canine tissue model of BS that T-wave alternans was caused by adjacent regions having action potentials (APs) with longer duration and larger domes or without domes coexisting simultaneously in the epicardium, and compared with the shallow T waves, deep T waves were associated with epicardial APs having longer durations and larger domes.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14] Furthermore, several reports demonstrate T-wave alternans in the 12-lead ECG after administration of class Ic antiarrhythmic drugs. [14][15][16][17][18] This case report describes a patient with asymptomatic BS in whom monophasic action potentials (MAPs) recorded from the RVOT demonstrated alternans and VF was induced only when the extrastimuli were applied after a shorter MAP of the alternans. …”
mentioning
confidence: 99%
“…This large spatial dispersion in epicardial AP morphology would not be expected when electrical coupling is normal. Still, some authors suggest that ST segment and T wave alternans after class I antiarrhythmic drugs [42,112] support the repolarization disorder hypothesis; however, whether this observation truly reflects a repolarization or depolarization disorder is unresolved.…”
Section: Heterogeneity In Repolarizationmentioning
confidence: 99%
“…Accordingly, pacing provided an effective therapy against bradycardia-related VT/VF onset in a Brugada syndrome patient [122]. Yet, ST elevations may also increase at fast heart rates [42,112,123,124]. While particular circumstances may be responsible (enhanced intermediate inactivation of the mutant Na channel [123] or the use of class IC antiarrhythmic drugs with use-dependence [42,112]), this phenomenon was also described in the absence of such confounders [42,112].…”
Section: Effects Of Heart Ratementioning
confidence: 99%
“…Ohkubo et al also described TWA in a patient with Brugada syndrome after class 1 antiarrhythmic drug (pilsicainide). TWA persisted for 15 min and was followed by microvolt TWA [19].…”
Section: T-wave Alternans In Patients With Brugada Syndromementioning
confidence: 99%